Development of Biology Teaching Material Supplements Based on the Potential of Gorontalo Karst Vegetation using a Biodiversity Literacy Approach - Abubakar Sidik Katili; Yuliana Retnowati; Ilyas H. Husain (Jurnal Penelitian Pendidikan IPA, 2025)
Vegetation is a community of plants of various species that live in a certain environmental condition and interactions occur in it. The fact of the vegetation analysis course material and has implications for students in vegetation analysis lecture activities. The development of teaching materials based on the potential of karst ecosystems can be carried out with a biodiversity literacy approach. The aims of this study to develop vegetation analysis materials supplements, by utilizing the results of vegetation analysis and their interaction with plant root microorganisms in karst ecosystems. The research mtheods used R&D method with the ADDIE model. The stages of research are analysis, design, development, implementation and evaluation. The results obtained showed that the form of supplement materials based on biodiversity literacy in the vegetation analysis course, had a validation result of 93.75% which was included in the range of 81% to 100%, in the aspect of design the supplement materials was 91.67% that indicated very good quality,with in the range 81% to 100%, the student response to the overall aspect in 94%, where this value is included in the very good category because it is in the range of 81 to 100%.